2003
DOI: 10.1177/1087057103008003007
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Repository Compound Stability in DMSO under Various Conditions

Abstract: The chemical stability of repository compounds is affected by various environmental conditions during long-term storage. Studies were carried out to evaluate the effects of the following potential causes of instability of compounds in DMSO at a 10-mM concentration: water, oxygen, freeze/thaw cycles, and storage container material. A set of compounds was selected for the study based on structural diversity and functional group representation. Compound concentration was determined with liquid chromatography/ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 8 publications
(11 reference statements)
1
84
0
Order By: Relevance
“…Given that both assay reagents and compounds in the screening collection may exhibit temporal variations in activity [30,31], we optimized the screening protocol to test each compound sample in the two individual fluorophore assays as closely in time as possible. There was no specific way within the robotic software to ensure that assay plates were run in an alternating fashion between the green and red systems, or set up any explicit dependencies or contingencies between the two assays.…”
Section: Interleaved Dual-assay Qhtsmentioning
confidence: 99%
“…Given that both assay reagents and compounds in the screening collection may exhibit temporal variations in activity [30,31], we optimized the screening protocol to test each compound sample in the two individual fluorophore assays as closely in time as possible. There was no specific way within the robotic software to ensure that assay plates were run in an alternating fashion between the green and red systems, or set up any explicit dependencies or contingencies between the two assays.…”
Section: Interleaved Dual-assay Qhtsmentioning
confidence: 99%
“…30 DMSO is hygroscopic and rapidly absorbs water from the atmosphere, and studies have shown that water uptake in compound DMSO solutions significantly contributes to compound degradation, precipitation, and reduction in concentration. 31,32 An open Echo source plate filled with 100% DMSO at under half capacity will equilibrate to a moisture content of over 30% within 24 h under standard laboratory conditions 23 ; therefore, storage conditions aimed at limiting hydration both prior to and during use are an important consideration. In AP, compound source plates for cell assays were created up to 1 week before the assay, foil sealed, and stored within a StoragePod nitrogen enclosure at 5% relative humidity (Roylan Developments Ltd., Leatherhead, Surrey, UK).…”
Section: Integrated Echo System I-postimplementation Enhancementsmentioning
confidence: 99%
“…Previous studies have typically characterized the stability of compounds in a lowvolume (<40 µL) 96-or 384-well plate format, which differ significantly from the high-volume (1.4-mL) Matrix tubes that Amgen has standardized for archive compound storage. 4,[6][7][8] As we will demonstrate, the labware format can affect the experimental parameters, so it is important to consider the storage vessel form factor in any stability validation study. We also wanted to characterize the effectiveness of a resolubilization protocol using a Covaris AFA platform.…”
mentioning
confidence: 99%